ANTS ALTER INSECTICIDE EFFICACY ON APHIDS IN THE YARD-LONG BEAN AGROECOSYSTEM ? (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
Ants Alter Insecticide Efficacy on Aphids in the Yard-Long Bean Agroecosystem? This study was aimed to detect the relationship between Aphis sp. and ants and to show whether ants could alter insecticide efficacy on Aphis sp. A survey was conducted in  the yard-long bean agroecosystems that have been frequently attacked by aphids and for years treated with imidacloprid insecticide (in Mulyosari Village, intensive sample) versus those barely treated in Ganjar Agung Village (non-intensive sample), both in the West Metro municipal area, Lampung. Two sampling occasions were made (in March and November 2005) where 35 plant parts (i.e. 35 flowers and 35 pods) per sample were randomly observed to record the number of Aphis sp. and ants. The efficacy of the insecticide treatment was determined by comparing the mean number of aphids or ants from intensive versus non intensive samples using a t-test at the 0.05 level. The relationships between ant and aphid numbers were determined by calculating their coefficients of correlation and testing them using a t-test at the 0.01 or 0.05 level. The study showed that the long-term application of the insecticide imidacloprid in the yard-long bean agroecosystem 1) might strengthen the relationship between Aphis sp. and ants (especially Solenopsis sp., Camponotus sp. and Paratopula sp.) and 2) was not effective to suppress  Aphis sp. number. Stronger Aphis sp. — ant symbiotic relationship might alter the insecticide efficacy on Aphis sp. in the agroecosystem.